Managerial responses to changes in fair value accounting for equity securities - Kim, Sehwa; Kim, Seil; Marquardt, Carol; Shin, Dongoh (Contemporary Accounting Research, 2025)
Accounting Standards Update (ASU) 2016‐01 requires that unrealized gains and losses on equity investments (equity‐URGL) previously recognized in other comprehensive income now be included in net income. Using a sample of public insurers, we examine how this accounting standard change influences managerial investment decisions, with a particular focus on the moderating effects of compensation contracting and financial reporting practices. We find that prior to ASU 2016‐01, equity‐URGL was positively associated with CEO compensation, but this association dissipates in the post‐adoption period, when equity‐URGL is more frequently excluded from CEO performance metrics. Despite purported concerns about increased earnings volatility due to the new reporting requirements, highly affected insurers do not significantly reduce the size or risk of their equity investment portfolios following ASU 2016‐01, particularly when compensation metrics exclude equity‐URGL. We also find that equity‐URGL is more frequently excluded from non‐GAAP earnings post‐adoption, suggesting that managers adjust financial reporting practices as a response to the change. Moreover, highly affected insurers maintain the size and risk of their equity portfolios when equity‐URGL is excluded from non‐GAAP earnings. These findings suggest that managerial responses to ASU 2016‐01 are influenced by a balance between incentive structures and the costs associated with adjusting investment strategies.